Formation and Characterization of Copper Nanocube-Decorated Reduced Graphene Oxide Film. (4th June 2017) - Khan, M. Z. H.; Rahman, M. A.; Yasmin, P.; Tareq, F. K.; Yuta, N.; Komeda, T.; Jahan, R. A.
Abstract : In this study, we present a new approach for the formation and deposition of Cu nanocube-decorated reduced graphene oxide (rGO-CuNCs) nanosheet on indium tin oxide (ITO) electrode using very simple method. Cubic Cu nanocrystals have been successfully fabricated on rGO by a chemical reduction method at low temperature. The morphologies of the synthesized materials were characterized by ultraviolet-visible (UV-vis) spectroscopy, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, and atomic force microscopy (AFM). The as-formed CuNCs were found to be homogeneously and uniformly decorated on rGO nanosheets. We demonstrated that the individual rGO sheets can be readily reduced and decorated with CuNCs under a mild condition using L-ascorbic acid (L-AA). Such novel ITO/rGO-CuNCs represent promising platform for future device fabrication and electrocatalytic applications.